Analysis of health funding and expenditure in the municipalities of Sergipe state, Brazil: an ecological study, 2005-2020 - Oliveira, Millena Barroso; de Oliveira, Vinícius Henrique Ferreira Pereira [UNESP]; Blumenberg, Cauane; da Silva, Douglas Teixeira; Herval, Álex Moreira; Paranhos, Luiz Renato (FapUNIFESP (SciELO), 2025)
OBJECTIVE: To analyze part of health funding and expenditure in the municipalities of Sergipe state. METHODS: This is an epidemiological, observational, ecological study, using Sergipe public health budget data, for the period 2005-2020. The units of analysis were the state's municipalities. The data were collected from the Public Health Budget Information System, based on the following indicators: municipal revenue from Brazilian National Health System funding transfers, municipality funded expenditure and total expenditure on health. Absolute average annual variance in revenue and expenditure indicators were estimated using linear least squares models weighted for variance. RESULTS: Data for the 75 municipalities of Sergipe were assessed. The analyses showed that, in 2020, the lowest amount of health transfer revenue was BRL 244.00 per inhabitant, transferred to São Cristóvão. The highest amount was BRL 743.00 per inhabitant, allocated to São Francisco. Health transfer revenue increased in all municipalities studied over the years analyzed, with an absolute average annual increase of BRL 23.00 per inhabitant. CONCLUSION: There was an absolute average annual increase in health transfer revenue allocated to municipalities. Transfer was uneven among the municipalities analyzed.